A history of world societies - MacKay, John P.; Hill, Bennett D.; Buckler, John; Ebrey, Patricia Buckley; Beck, Roger B.; Crowston, Clare Haru; Wiesner, Merry E. (Bedford/St. Martin's, 2012)
The earliest human societies, to 2500 B.C.E. -- The rise of the state in Southwest Asia and the Nile Valley, 3200-500 B.C.E. -- The foundation of Indian society, to 300 C.E. -- China's classical age, to 221 B.C.E. -- The Greek experience, 3500-100 B.C.E. -- The world of Rome, 750 B.C.E.-400 C.E. -- East Asia and the spread of Buddhism, 221 B.C.E.-800 C.E. -- Continuity and change in Europe and Western Asia, 200-850 -- The Islamic world, 600-1400 -- African societies and kingdoms, 1000 B.C.E.-1500 C.E. -- The Americas, 2500 B.C.E. -1500 C.E. -- Cultural exchange in Central and Southern Asia, to 1400 -- States and cultures in East Asia, 800-1400 -- Europe in the Middle Ages, 850-1450 -- Europe in the Renaissance and Reformation, 1350-1600 -- The acceleration of global contact, 1450-1600 -- European power and expansion, 1500-1750 -- New worldviews and ways of life, 1540-1790 -- Africa and the world, 1400-1800 -- The Islamic world powers, 1300-1800 -- Continuity and change in East Asia, 1400-1800 -- Revolutions in the Atlantic world, 1775-1815 -- The revolution in energy and industry, ca. 1760-1860 -- Ideologies of change in Europe, 1815-1914 -- Africa, Southwest Asia, and the new imperialism, 1800-1914 -- Asia in the era of imperialism, 1800-1914 -- Nation building in the Americas and Australia, 1770-1914 -- World War and revolution, 1914-1929 -- Nationalism in Asia, 1914-1939 -- The Great Depression and World War II, 1929-1945 -- Global recovery and division between superpowers, 1945 to the present -- Independence, progress, and conflict in Asia and the Middle East, 1945 to the present -- The global South: Latin America and Africa, 1945 to the present -- A new era in world history -- Timeline: A history of world societies : an overview.